2021
DOI: 10.1038/s41467-021-25106-4
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM structures of the TTYH family reveal a novel architecture for lipid interactions

Abstract: The Tweety homologs (TTYHs) are members of a conserved family of eukaryotic membrane proteins that are abundant in the brain. The three human paralogs were assigned to function as anion channels that are either activated by Ca2+ or cell swelling. To uncover their unknown architecture and its relationship to function, we have determined the structures of human TTYH1–3 by cryo-electron microscopy. All structures display equivalent features of a dimeric membrane protein that contains five transmembrane segments a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 61 publications
(87 reference statements)
0
28
1
Order By: Relevance
“…In contrast to the tetrameric stoichiometry we observed in the cellular environment, the recent structures of members of the TTYH family shared a dimeric organization 14 , 15 . However, as these structures were determined following membrane solubilization by detergents, we hypothesized that this process may result in the dissociation of TTYH complexes.…”
Section: Resultscontrasting
confidence: 87%
See 4 more Smart Citations
“…In contrast to the tetrameric stoichiometry we observed in the cellular environment, the recent structures of members of the TTYH family shared a dimeric organization 14 , 15 . However, as these structures were determined following membrane solubilization by detergents, we hypothesized that this process may result in the dissociation of TTYH complexes.…”
Section: Resultscontrasting
confidence: 87%
“…While in situ cross-linking indicated that mTTYH proteins are composed of multiple subunits, we cannot exclude the possibility that heteromeric assembly formation of mTTYH dimers 14 , 15 with additional endogenous proteins underlies the observed migration patterns. Thus, to directly examine the number of mTTYH subunits within a complex in living cells, we resorted to the single-molecule subunit counting approach 22 .…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations